Xylem conduit deformation across vascular plants: an evolutionary spandrel or protective valve? - Zhang, Yong‐Jiang; Hochberg, Uri; Rockwell, Fulton E.; Ponomarenko, Alexandre; Chen, Ya‐Jun; Manandhar, Anju; Graham, Adam C.; Holbrook, N. Michele (The New phytologist, 2023)
Summary The hydraulic system of vascular plants and its integrity is essential for plant survival. To transport water under tension, the walls of xylem conduits must approximate rigid pipes. Against this expectation, conduit deformation has been reported in the leaves of a few species and hypothesized to function as a ‘circuit breaker’ against embolism. Experimental evidence is lacking, and its generality is unknown. We demonstrated the role of conduit deformation in protecting the upstream xylem from embolism through experiments on three species and surveyed a diverse selection of vascular plants for conduit deformation in leaves. Conduit deformation in minor veins occurred before embolism during slow dehydration. When leaves were exposed to transient increases in transpiration, conduit deformation was accompanied by large water potential differences from leaf to stem and minimal embolism in the upstream xylem. In the three species tested, collapsible vein endings provided clear protection of upstream xylem from embolism during transient increases in transpiration. We found conduit deformation in diverse vascular plants, including 11 eudicots, ginkgo, a cycad, a fern, a bamboo, and a grass species, but not in two bamboo and a palm species, demonstrating that the potential for ‘circuit breaker’ functionality may be widespread across vascular plants.